PRINCIPLES AND QUALITIES OF LEADERSHIP - Riak , Dr Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Leadership in the army is principally about doing things. It is a business of applying your professional skill and knowledge and your ability to inspire people to get things done. Leadership is a blend of persuasion, compulsion and example, a combination that makes men to do what their commanders want of them even when the task is not essentially to their liking. More can be achieved by persuasion, encouragement and example rather than by compulsion, although on occasions compulsion is necessary especially when men are tired and frightened. Soldiers will instinctively obey a forceful command from a strong commander with the necessary character, knowledge and experience.